PENGARUH PERILAKU BELAJAR, PENGENDALIAN DIRI, MOTIVASI, EMPATI, KETERAMPILAN, DAN KEPERCAYAAN DIRI TERHADAP PRESTASI AKADEMIK MAHASISWA PRODI AKUNTANSI UNIVERSITAS PEMBANGUNAN PANCA BUDI MEDAN - Heriyati Chrisna (Jurnal Akuntansi Bisnis dan Publik, 2019)
The purpose of this study is to prove empirically the effect of learning behavior, self-control, motivation, empathy, skills, and self-confidence in academic achievement of Accounting Study Program Students at Panca Budi Development University Medan. The population and sample in the study were Stambuk 2015/2018 6th semester students, accounting courses totaling 307 students. The technique in sampling uses random sampling techniques. The sample in this study were 75 students. Data collection by distributing questionnaires. Data analysis using multiple linear regression using SPSS Version 19.0. The results of this study indicate that learning behavior, self-control, motivation, empathy, skills, and self-confidence have a simultaneous influence on student academic achievement. Partially learning behavior, self-control, empathy, skills and self-confidence do not affect student academic achievement. While motivation has a partial effect on student academic achievement.